Determining Factors for Pharmaceutical Innovation and the Health Industrial Complex in Brazil and the BRICS - Leal, Guilherme Arevalo; Bresciani, Luis Paulo; Machado, Celso (International Journal of Business, Economics and Management, 2022)
The development of a local pharmaceutical research and development industry is essential to meet the demands of a large country with a large population such as Brazil. This work aims to explore the existing data on the ecosystem of the pharmaceutical industry in this group of countries, and through parameters based on the precursor literature, to identify the innovation factors and the position of Brazil in relation to the other representatives of the BRICS (the leading developing countries in the world). Since the mid-1940s, Brazil has received pharmaceutical multinationals and through government initiatives it has locally reproduced medicines developed abroad when the patents have ended. The BRICS represent the group of emerging countries considered “the big five”, with population capacity and economic growth that tend to boost the global economy in the coming years. The comparative analysis showed that Brazil has a certain lag in fundamental parameters for the existence of a national pharmaceutical R&D industry, having placed behind Russia, India and China, even symbolically by not producing a national vaccine in response to COVID-19.